Antibacterial Efficacy of Cold Atmospheric Plasma, Photodynamic Therapy with Two Photosensitizers, and Diode Laser on Primary Mandibular Second Molar Root Canals Infected with Enterococcus faecalis: An In Vitro Study - Leyli Haghighi; Arash Azizi; Mehdi Vatanpour; Gholamhossein Ramezani (Hindawi Limited, 2023)
Objectives. This study aimed to compare the antibacterial efficacy of cold atmospheric plasma (CAP), photodynamic therapy (PDT) with two photosensitizers (PSs), and diode laser for disinfection of primary mandibular second molar root canals infected with Enterococcus faecalis (E. faecalis). Materials and Methods. In this in vitro experimental study, 50 primary second primary molars underwent chemomechanical preparation of root canals. The root canals were then inoculated with E. faecalis. After 3 weeks of incubation, the teeth were randomly assigned to five groups of CAP, 940 nm diode laser, PDT with 445 nm laser and curcumin PS, PDT with 660 nm laser and methylene blue (MB) PS, and 2.5% sodium hypochlorite (NaOCl). Samples were collected from the vortexed root canals and cultured on agar, and the number of colonies was counted. Data were analyzed by one-way analysis of variance. Results. The percentage of reduction in bacterial count was significantly different among the study groups (P<0.001). The highest reduction in bacterial count was noted in 2.5% NaOCl and the lowest in 940 nm diode laser group. The difference in bacterial count reduction between 445 nm laser + curcumin and 660 nm laser + MB (P=0.989), and CAP and NaOCl (P=1.000) groups was not significant. Conclusion. CAP was found to be more effective than PDT and diode laser as an adjunct to mechanical root canal disinfection of primary molars for elimination of E. faecalis and can serve as an alternative to 2.5% NaOCl irrigation.